2020
DOI: 10.20945/2359-3997000000227
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum levels of IL-27and IL-35 in patients with Graves disease

Abstract: Objectives: Graves' disease (GD) is an autoimmune disease causing the overproduction of the thyroid hormone from thyroid gland. This disease is mainly the result of the production of antibodies against TSH receptors. Cytokines play an important role in orchestrating the pathophysiology in autoimmune thyroid disease. The regulatory role of IL-12 on TH1 cells has been proven. IL-27 and IL-35, members of IL-12 cytokine family, are two cytokines that have been newly discovered. IL-35 has been identified as a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…In addition, some studies show that antithyroid drugs can reduce the production of thyroid pro‐inflammatory cytokines 4 . An increasing number of studies have suggested that pro‐inflammatory cytokines, such as interleukin (IL)‐35, IL‐29, IL‐27, and tumor necrosis factor (TNF)‐α, may be involved in the development of GD 5–8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies show that antithyroid drugs can reduce the production of thyroid pro‐inflammatory cytokines 4 . An increasing number of studies have suggested that pro‐inflammatory cytokines, such as interleukin (IL)‐35, IL‐29, IL‐27, and tumor necrosis factor (TNF)‐α, may be involved in the development of GD 5–8 …”
Section: Introductionmentioning
confidence: 99%
“… 4 An increasing number of studies have suggested that pro‐inflammatory cytokines, such as interleukin (IL)‐35, IL‐29, IL‐27, and tumor necrosis factor (TNF)‐α, may be involved in the development of GD. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…GWAS genes in the modules associated with these traits were enriched for lymphocyte activation and differentiation and TCR signaling and cell-cell adhesion (e.g., PTPRC, IL2RA, IL7R, IFNG, FASLG, Figure 6E), with IL-35 signaling genes enriched in hypothyroidism and IBD, consistent with IL-35 upregulation in Hashimoto's thyroiditis (Yilmaz et al, 2016) and IBD (Y. Li et al, 2014)) and downregulation in Graves' disease (Saeed et al, 2021). The cardiovascular traits group included hypertension, atrial fibrillation, mean arterial pressure and renin-angiotensin system, was associated with pericytes/smooth muscle cells (SMCs, responsible for modulating total peripheral resistance in arterioles), and was enriched with blood circulation, smooth muscle contraction, muscle structure development and cardiocyte differentiation genes (e.g., CACNA1C, CACNA1D, CASQ2, PLN).…”
Section: Associating Gwas Genes With Gene Programs Across Cell Types Reveals Six Main Trait Groupsmentioning
confidence: 68%
“…Our data suggest a possible detrimental effect of IL-27, which is likely to contribute to the development of autoimmune thyroid disease in individuals with T1DM. In contrast, a recent study found reduced IL-27 serum levels in patients with Graves' disease, suggesting a possible anti-inflammatory role of these cytokines [46]. A possible explanation for these differences is the effect of IL-27 on the Th1 to Th2 ratio [47], which is dominant in HD, whereas it is non-dominant in Graves' disease [48].…”
Section: Discussionmentioning
confidence: 86%